2019
DOI: 10.3390/w12010047
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Land Use and Land Cover on Water Quality at Multiple Buffer-Zone Scales in a Lakeside City

Abstract: Understanding the effect of land use/land cover (LULC) on water quality is essential for environmental improvement, especially in urban areas. This study examined the relationship between LULC at buffer-zone scales and water quality in a lakeside city near Poyang Lake, which is the largest freshwater lake in China. Representative indicators were selected by factor analysis to characterize the water quality in the study area, and then the association between LULC and water quality over space and time was quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 38 publications
1
17
0
1
Order By: Relevance
“…The performance of land cover metrics in water quality prediction, calculated for different spatial scales with even additional distance of flow accumulation scaling, was previously broadly discussed [42,45,92]. However, the presented results are not clear and unequivocal.…”
Section: Land Cover Effect On Nutrient Variabilitymentioning
confidence: 77%
See 1 more Smart Citation
“…The performance of land cover metrics in water quality prediction, calculated for different spatial scales with even additional distance of flow accumulation scaling, was previously broadly discussed [42,45,92]. However, the presented results are not clear and unequivocal.…”
Section: Land Cover Effect On Nutrient Variabilitymentioning
confidence: 77%
“…In such a way, a number of studies linked the concentration of nutrient compounds with landscape properties and these relationships were studied at different spatial scales, from entire catchment areas [39] to buffer zones along the watercourses [40,41], sometimes with additional distance or flow accumulation scaling [42]. Most of the work in this area, however, concerned catchments of over a hundred square kilometers, including upland or highland relief and steeper slopes of the terrain, where high hydrological connectivity and intensive erosion result in increased ion migration [43][44][45]. Meanwhile, few studies used widely available land cover datasets [39], while in most cases land cover metrics were computed with the use of government or self-classification-based land cover maps [46,47], making the results not comparable at the European scale.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the effects of distance from the lake can improve the water quality change 95 , 96 . Huang et al 97 suggested that the different land use types exclusively croplands and built-up should be put to quite some distance away from the water bodies. For this, a set of equidistant buffer zones of some distances to sampling sites can support the understanding of the impacts of land-use types on the concentration of different pollutants because the association between these types and the water quality parameters may change as the distance to water body increases.…”
Section: Discussionmentioning
confidence: 99%
“…This study illustrates that terrestrial determinants considerably affect stream health at 500m buffer and subbasin scale [32]. The developed linear models between terrestrial determinants and water quality parameters can be used in policy making at watershed scale to improve stream health.…”
Section: Ecological and Management Implicationsmentioning
confidence: 86%